Anharmonicity induced faster decay of hot phonons in rutile TiO2 nanorods: a Raman spectromicroscopy study. Issue 3 (5th January 2022) - Rani, Chanchal; Pathak, Devesh K.; Tanwar, Manushree; Kandpal, Suchita; Ghosh, Tanushree; Maximov, Maxim Yu.; Kumar, Rajesh
Abstract : Temperature-dependent Raman spectromicroscopy of rutile TiO2 nanorods has been studied here to understand the effect of thermal perturbations on different Raman-active phonon modes. Abstract : Temperature-dependent Raman spectromicroscopy of rutile TiO2 nanorods has been studied here to understand the effect of thermal perturbations on different Raman-active phonon modes. The TiO2 nanorods, characterized using electron microscopy, X-ray diffraction and Raman spectroscopy, were prepared using a hydrothermal method. Raman spectra, recorded at temperatures higher than room temperature, have been analyzed within the theoretical framework developed by considering the anharmonicity of hot phonons. Different temperature-dependent responses were observed for Eg and A1g modes with the latter being immune with respect to the Raman peak position. The experimental results indicated a dominant role of phonon–phonon kinematics on peak shifts and broadenings in the Eg Raman mode, confirming the prevalence of the anharmonic effect. The temperature-dependent redshift in the peak position and broadening of the Raman Eg mode have been explained using three or four phonon decay processes. A consolidated insight, by showing a good agreement between experimental and theoretical frameworks, about the behavior of phonons under the influence of elevated temperatures has been presented.